Online Advertising and Consumer Engagement for low and high involvement purchase decisions - Mhlaba, Nontuthuko Emelda (University of the Witwatersrand, Johannesburg, 2024)
This research studies the relationship between online banner advertising, consumer engagement dimensions and low and high involvement purchase decisions. Advertising influences customer engagement (Daven and Sari, 2021), and consumer engagement for online banner advertisements is expressed differently depending on purchase context i.e. high and low involvement products. Marketers use a similar approach to advertise low and high involvement products online, without differentiating how affective and cognitive dimensions of engagement influence consumer purchase decisions for low and high involvement products. Using the elaboration likelihood model, the study proposes that online advertising and consumer engagement dimensions, specifically the cognitive and affective dimensions, affect low and high involvement purchase decisions significantly. A self-administered survey designed on Qualtrics was distributed via online channels such as WhatsApp, LinkedIn, Facebook, and Instagram. Using a random snowball sampling method, a total of 305 responses were collected. The study tested 8 hypotheses and data from the study was analysed using structural equation modelling on SPSS. The results of the study indicate that online banner advertising has a significant relationship with cognitive and affective consumer engagement for high and low involvement products. The results also reveal that cognitive and affective consumer engagement has a positive relationship with both low and high involvement purchase decisions. The study confirms that dimensions of engagement do influence online advertising outcomes as well as purchase decisions for low and high involvement products. This study contributes to theoretical literature on online advertising and dimensions of consumer engagement in low and high involvement purchase contexts, the study also has practical implication in that it broadens marketers’ awareness of cognitive and affective engagement influences on high and low involvement purchase decisions, specifically for online banner adverts.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in Strategic Marketing to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Online Advertising; Consumer Engagement; Low and high involvement purchase decisions; UCTD; SDG-8: Decent work and economic growth